Prototype Smart Parking Lift System Berbasis Arduino - Aprinal Adila Asril; Popy Maria - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2018)
High number of vehicle theft and damaged vehicle caused climate factor such disasters on conventional garage has made an encouragement to the owners to decrease those risks. By using special access and by putting the garage down tothe basement can be trusted way to minimalized those risks above.This system works by communicate RFID reader and infrared sensor an inputs. RFID reader MFRC522 has a role as authentication tool for vehicle owners by manifest their card identities to the system. Meanwhile the infrared sensors IR-FC51 work as the input of automatic system. All these inputs will be proceeded by Arduino Uno as smart system data processor and ended by the movement of the dc motor as the lift motor and LCD as the information displayer.The registered owner card will get a special access to entering parking lot on basement, while the users that didn’t have registered card has no access to enter. Inside the lift, there will be infrared sensors to detect the vehicle on the lift and automatically will moved the lift upside or downside.